The Unexplored Potential of Trade in Services in Africa : From Hair Stylists and Teachers to Accountants and Doctors - Dihel, Nora (World Bank, Washington, DC, 2016)
The book speaks volumes about the latent potential for trade in services in Africa and the regulatory hurdles that providers face in materializing such flows, and proposes concrete policy action for integrating fragmented services markets in Africa. The contributions to this volume seek to shed some light on uncharted opportunities for services trade in Africa, and invigorate and deepen the discussion about the role of services in trade diversification and economic upgrading on the continent. The focus is on less explored areas such as informal trade in services and trade in more sophisticated but equally neglected sectors such as professional services, education and health services, and services related to mining that are rarely associated with services trade in Africa. Novel data collection methods such as crowdsourcing and mystery shopping, pioneering knowledge transfer practices and experiences with innovative policy reforms applied to both modern and traditional services sectors are explored to draw attention to available assessment tools and policy instruments for possible refinement and broader application across sectors.